Risk Stratification and Distribution of Hepatocellular Carcinomas in CEUS and CT/MRI LI-RADS: A Meta-Analysis - Zhou, Yan; Qin, Zhengyi; Ding, Jianmin; Zhao, Lin; Chen, Ying; Wang, Fengmei; Jing, Xiang (Frontiers in Oncology, 2022)
Background: CEUS LI-RADS and CT/MRI LI-RADS have been used in clinical practice for several years. However, there is a lack of evidence-based study to compare the proportion of Hepatocellular carcinomas (HCCs) in each category and the distribution of HCCs of these two categorization systems. Purpose: To compare the proportion of HCCs between corresponding CEUS LI-RADS and CT/MRI LI-RADS categories and the distribution of HCCs and non-HCC malignancies in each category. Methods: We conducted a search on PubMed, Embase, and Cochrane Central database from January 2014 to October 2020. The proportion of HCCs and non-HCC malignancies and the corresponding sensitivity, specificity, accuracy, diagnostic odds ratio (DOR) and area under curve (AUC) of the LR-5 and LR-M categories were determined using a random effect model. Results: A total of 34 studies were included. The proportion of HCCs in CEUS LR-5 was 97%, and in CECT/MRI LR-5, 95% (P>0.05). The proportion of non-HCC malignancy in CEUS LR-M was lower than that of CECT/MRI LR-M (41% vs 61%, P =0.02). The sensitivity, specificity and accuracy of CEUS LR-5 for HCCs were 0.73, 0.94 and 0.80, respectively, and of CECT/MRI LR-5 for HCCs, 0.69, 0.92 and 0.76, respectively. Conclusion: With the upshift of LI-RADS category, the proportion of HCCs increased. CEUS and CECT/MRI have similar positive predictive values for HCCs in LR-1–5 categories. CEUS LR-5 and CECT/MRI LR-5 have similar diagnostic performance for HCCs. CEUS LR-M have higher proportion of HCCs and lower proportion of non-HCC malignancies compared with CECT/MRI LR-M.